1971
DOI: 10.1128/jb.107.1.268-294.1971
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy of Marine Bacteria: the Genus Beneckea

Abstract: One-hundred-and-forty-five isolates of marine origin were submitted to an extensive physiological, nutritional, and morphological characterization. All strains were gram-negative, facultatively anaerobic, straight or curved rods which were motile by means of flagella. Glucose was fermented with the production of acid but no gas. Sodium but no organic growth factors were required. None of the strains were able to denitrify or fix molecular nitrogen. The results of nutritional and physiological tests were submit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
134
1
2

Year Published

1981
1981
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 316 publications
(143 citation statements)
references
References 54 publications
6
134
1
2
Order By: Relevance
“…However, certain Vr'brio spp. also metabolize short chain volatile fatty acids, alcohols, and aromatic hydrocarbons (Baumann et al 1971), and plasmidcontaining Vibrio spp. have been isolated from Gulf of Mexico oil fields in significantly larger numbers than from non-oil-impacted control areas (Hada & Sizemore 1981).…”
Section: Discussionmentioning
confidence: 99%
“…However, certain Vr'brio spp. also metabolize short chain volatile fatty acids, alcohols, and aromatic hydrocarbons (Baumann et al 1971), and plasmidcontaining Vibrio spp. have been isolated from Gulf of Mexico oil fields in significantly larger numbers than from non-oil-impacted control areas (Hada & Sizemore 1981).…”
Section: Discussionmentioning
confidence: 99%
“…When required, gentamycin was added to the agar plates. For all growth experiments, strains of R. pomeroyi were cultivated in defined basal minimal medium (Baumann et al, 1971). This medium had the following composition: 50 mM MOPS (pH 7.5), 200 mM NaCl, 10 mM KCl, 330 mM K 2 HPO 4 , 10 mM CaCl 2 , 50 mM MgSO 4 and 100 mM FeSO 4 .…”
Section: Media and Growth Conditionsmentioning
confidence: 99%
“…Strains were screened for their ability to utilize 62 different compounds as 'the sole organic source of carbon for growth by the methods of but with the use of a modification of the minimal medium of Clowes & Hayes (1968). This basal medium was chosen after pilot studies had shown that it gave better growth of the majority of strains studied than did the basal medium BM of Baumann et al (1971) which we had used previously. The basal medium contained (g/l): NH4C1, 5.0; NH4N03, 1.0; Na2S04, 2.0; K2HP04, 3.0; KH2P04, 1.0; MgS04.7H20, 0.1; NaCl, 10.0; MgC12.…”
Section: Nutritional Screeningmentioning
confidence: 99%